An examination of the works of Ancient voices by Michael Sweeney, The headless horseman by Timothy Broege and Cut to the chase by Todd Stalter - Hankey, Joshua D. (Kansas State University, 2013)
This document is based on the preparation, rehearsal, and performance of selected pieces for the Graduate Conducting recital of Joshua D. Hankey. The pieces examined in the theoretical and historical analysis for this report are Ancient Voices by Michael Sweeney, The Headless Horseman by Timothy Broege and Cut to the Chase by Todd Stalter. This document also contains rehearsal plans and procedures for the preparation of the literature. The recital was performed on May 9, 2013 in the Santa Fe Trail Middle School Gymnasium on the campus of Santa Fe Trail Middle School, and was performed by the members of the Santa Fe Trail Middle School 7th grade Intermediate Band, and the Santa Fe Trail Middle School Concert Band.
Keywords: Ancient Voices; The Headless Horseman; Cut to the Chase; Michael Sweeney; Timothy Broege; Todd Stalter; Music (0413)